Analysis of research records for leprosy treatment in a basic health unit (Research, Society and Development, 2021)
Leprosy is a chronic disease, caused by Mycobacterium leprae, which affects the skin causing lesions. However, the infectious agent also has a predilection for peripheral nerves, causing impairment of motor functions when left untreated. Early diagnosis is essential for controlling and eliminating the disease. Therefore, for an adequate drug therapy, guidance is necessary. This research aimed to analyze the pharmacological and non-pharmacological treatment of individuals with leprosy registered in a basic health unit (UBS) in the South Zone of the city of Teresina, Piauí, over a period of 10 years (2011-2021) by evaluation of medical records and, consequently, evaluation of their quality of life and form of adherence to therapy. The study was a retrospective cross-sectional descriptive documentary research, with a qualiquantitative approach, in which data were collected through the assessment of the medical records of patients treated in the period from 2011 to 2021. if the absence of the pharmaceutical care service and its direct contribution to the ineffectiveness of pharmacological and non-pharmacological treatment for leprosy, added to the patients' lack of real knowledge about the pathology - which corroborated the difficulty of adherence to treatment, added the preventable adverse effects caused by multidrug therapy, thus demonstrating once again the need for the pharmacist to be jointly responsible for the drug therapy of the patient being treated for leprosy.